PEMBANGUNAN SISTEM INFORMASI SIMPAN PINJAM PADA LPD DESA ADAT TENGKULUNG - Putu Diah Rahayu Dewi; Eddy Muntina Dharma; I Made Artana (LPPM Universitas Dhyana Pura, 2023)
ABSTRACTIn helping village community businesses, there are LPDs that provide convenience in providing savings and loan services. Along with the progress of the development of the LPD which is getting faster and faster, the complexity of processing savings and loan transaction data is getting higher, such as the LPD in Tengkulung Traditional Village which is located on Jalan. Setra Ganda Mayu, South Kuta District, Badung Regency. Recording data manually with this book often encounters problems in the process of calculating data and reports, given the large amount of data that must be processed manually, resulting in errors in preparing reports. So, with the development of the current information technology era, the development of a computerized system, namely